[Let's make a deal ; Ordinary people ; Two for the road [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1990)
Deals with the negotiations of the PCGG on the ill-gotten wealth of the Marcoses; the causes of learning disabilities of children and the thirty-eight years of the singing career of the Reycard Duet.
Let's make a deal (16 min.) -- Ordinary people (19 min.) -- Two for the road (10 min.).
VHS.
Keywords: Reycard Duet; Political corruption -- Philippines; Learning disabilities; Singers -- Philippines